EFISIENSI SEKTOR INDUSTRI DAERAH KABUPATEN DAN KOTA DI PROPINSI JAWA TIMUR - Ida Nuraini (MediaTrend, 2022)
The intense global competition requires the industrial sector to produce efficiently. Industrial efficiency is determined not only by internal factors but also by external factors. This study aims to measure industrial efficiency in regencies and cities in East Java Province and to determine the determining variables of industrial efficiency so that it can be used as material for government policy in the development of the industrial sector. The data used is secondary data sourced from the Central Statistics Agency. Meanwhile, the analysis tools used are efficiency analysis and multiple regression analysis with panel data. The results showed that in general the industrial sector in districts and cities in East Java was not efficient. Meanwhile, the external variables that affect the efficiency of the industrial sector are the inflation variable and the district/city minimum wage. Regional governments are expected to be able to control inflation in their regions and be able to determine district/city minimum wages that can benefit both the industrialsector and workers.